Philosophy of the sign - Simon, Josef, 1930- (SUNY series in contemporary continental philosophy., 1995)
In this book, Simon wields Ockham's razor like a scythe to argue historically and systematically for a coherent philosophy of the sign as sign with an unprecedented minimum of ontological and semantical commitments. Deconstructing Plato, Frege, and Husserl, he accounts for signs without positing the existence either of meanings which they express or of things to which they refer. Indeed, he shows that one cannot understand anything that is not a sign, so that one never gets to meanings without signs or things beyond signs.